2022 American College of Rheumatology/EULAR classification criteria for Takayasu arteritis. Issue 12 (9th November 2022) - Grayson, Peter C; Ponte, Cristina; Suppiah, Ravi; Robson, Joanna C; Gribbons, Katherine Bates; Judge, Andrew; Craven, Anthea; Khalid, Sara; Hutchings, Andrew; Danda, Debashish; Luqmani, Raashid A; Watts, Richard A; et al.
Abstract : Objective: To develop and validate new classification criteria for Takayasu arteritis (TAK). Methods: Patients with vasculitis or comparator diseases were recruited into an international cohort. The study proceeded in six phases: (1) identification of candidate criteria items, (2) collection of candidate items present at diagnosis, (3) expert panel review of cases, (4) data‐driven reduction of candidate items, (5) derivation of a points‐based classification score in a development data set and (6) validation in an independent data set. Results: The development data set consisted of 316 cases of TAK and 323 comparators. The validation data set consisted of an additional 146 cases of TAK and 127 comparators. Age ≤60 years at diagnosis and imaging evidence of large‐vessel vasculitis were absolute requirements to classify a patient as having TAK. The final criteria items and weights were as follows: female sex (+1), angina (+2), limb claudication (+2), arterial bruit (+2), reduced upper extremity pulse (+2), reduced pulse or tenderness of a carotid artery (+2), blood pressure difference between arms of ≥20 mm Hg (+1), number of affected arterial territories (+1 to +3), paired artery involvement (+1) and abdominal aorta plus renal or mesenteric involvement (+3). A patient could be classified as having TAK with a cumulative score of ≥5 points. When these criteria were tested in the validation data set, the model area under the curve was 0.97 (95% CI 0.94 to 0.99) with a sensitivity of 93.8% (95% CI 88.6% to 97.1%) and specificity of 99.2% (95% CI 96.7% to 100.0%). Conclusion: The 2022 American College of Rheumatology/EULAR classification criteria for TAK are now validated for use in research.